2015
DOI: 10.1016/j.envres.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Chemical exposure reduction: Factors impacting on South African herbicide sprayers' personal protective equipment compliance and high risk work practices

Abstract: The high exposure risks of workers to herbicides in low- and middle-income countries is an important public health concern because of the potential resulting negative impacts on workers' health. This study investigated workers' personal protective equipment (PPE) compliance as a risk mitigation measure; particularly workers who apply herbicides for Working for Water (WfW) - a South African invasive alien vegetation control programme. The study aim was to understand workers' low PPE compliance by analysing thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 60 publications
0
31
0
1
Order By: Relevance
“…These findings were in conformity with that by Tamrin and Jamiluddin (2014) who reported that the knowledge score of pesticide management was high; however, the practice score, especially the use of personal protective equipment (PPE), was very poor 21) . In addition, the study by Yuantari et al (2015) suggested that almost none of the farmers used standardized PPE and used PPE completely 22) .Itmay be due to the high cost of PPE, hot tropical climatic conditions, poverty, or lack of training programs by the government 21,[23][24][25] . Some farmers had an inappropriate protective behavior, such as eating, drinking, smoking, taking a break, blowing or sucking a spray nozzle with their mouth, and spraying when it was windy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in conformity with that by Tamrin and Jamiluddin (2014) who reported that the knowledge score of pesticide management was high; however, the practice score, especially the use of personal protective equipment (PPE), was very poor 21) . In addition, the study by Yuantari et al (2015) suggested that almost none of the farmers used standardized PPE and used PPE completely 22) .Itmay be due to the high cost of PPE, hot tropical climatic conditions, poverty, or lack of training programs by the government 21,[23][24][25] . Some farmers had an inappropriate protective behavior, such as eating, drinking, smoking, taking a break, blowing or sucking a spray nozzle with their mouth, and spraying when it was windy.…”
Section: Discussionmentioning
confidence: 99%
“…For the communication to be effective, it is necessary to know the characteristics of the event that represents the risk to be communicated. For this reason, the dialogic explanation was built on the basis of clinical evidence on the prevention of health disorders when pesticides are used during rural work (4,10) . Risk communication took place over two days in April 2014, only in Municipality 1, in the presence of 16 rural workers each day.…”
Section: Study Protocolmentioning
confidence: 99%
“…An apparently simply strategy to reduce the exposure of workers during application of and throughout the rural labor process with pesticides is the use of personal protective equipment (PPE). A study carried out in South Africa showed that workers have low adherence to the use of PPE during the application of pesticides, despite knowing the risks of unprotected exposure (10) . It is important to note that rural workers who apply pesticides are the most exposed, although those who work in the plantation after the application of these products and the families of those who apply them, even with PPE/recommended clothing, are also exposed to the risks.…”
Section: Introductionmentioning
confidence: 99%
“…The WfW programme, which is one of the world's biggest for controlling invasive vegetation, is regarded as successful in providing skills and training to unemployed populations from low-income communities [42]. There have been concerns, however, about worker safety in relation to exposure to occupational hazards [43]. For example, exposure to herbicides is theoretically mitigated using PPE.…”
Section: Working For Water Programmementioning
confidence: 99%
“…PPE use was found to be influenced by workers' socio-cultural context (i.e., gender dynamics and social status), workers' risk perception of herbicide use, and their environmental and logistical working conditions. The findings suggested that interventions other than PPE promotion, such as engineering or administrative controls, should be explored [43]. This is of relevance due to the distinct possibility that even with 'perfect' adherence to PPE, its use in relation to unavoidable dangerous heat and sun exposure may increase the risk of adverse events compared to not using PPE at all.…”
Section: Working For Water Programmementioning
confidence: 99%